Integrating technology, Javanese ethnomathematics, and realistic mathematics education in supporting prospective mathematics teachers' numeracy skills: A learning trajectory - Nursyahidah, Farida; Wardono; Mariani, Scolastika; Wijayanti, Kristina (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
In the era of the 21st century and Industrial Revolution 4.0, prospective mathematics teachers (PMTs) are expected not only to possess strong mathematical content knowledge but also to develop pedagogical approaches that promote students’ numeracy skills in meaningful and contextually relevant ways. However, despite growing global attention to numeracy, there remains a gap in instructional models that effectively integrate local cultural contexts and technological tools in the preparation of PMTs. Addressing this gap, this study introduces a novel learning trajectory that embeds technology, Javanese ethnomathematics, and Realistic Mathematics Education into a coherent instructional design framework, namely TE-RME aimed at enhancing PMTs' numeracy competencies. The research employed a design research methodology encompassing three iterative stages: preliminary design, design experiments consisting of a pilot and teaching experiment, and retrospective analysis. The participants were 25 fifth-semester PMTs enrolled at a private university in Semarang, Indonesia. The resulting trajectory comprises five learning activities, such as orientation to cultural contexts, exploration and problem-solving of numeracy tasks, task design involving numeracy elements, communication and interpretation of mathematical solutions, and instructional design involving the integration of numeracy tasks. Findings revealed that the TE-RME approach effectively supported PMTs in making meaningful connections between culturally embedded practices and everyday mathematical reasoning. By engaging with authentic local contexts, students demonstrated increased fluency in solving numeracy problems and designing contextually relevant learning activities. This research contributes a culturally responsive instructional model for mathematics teacher education and underscores the pedagogical potential of integrating local wisdom with contemporary mathematics education approaches. Implications point to further research exploring other ethnomathematical contexts to enrich mathematics instruction and promote equitable and culturally grounded mathematics learning.